Diagnostic accuracy of combined sonographic findings and pleural fluid adenosine deaminase levels for tuberculous pleural effusions in endemic areas - A study of 415 patients (Journal of Fatima Jinnah Medical University, 2019)
Background: Pleural fluid adenosine deaminase (ADA) level is a useful test for differentiating tuberculous from malignant pleural effusions. Trans-thoracic ultrasound (TUS) is currently being used to identify pleural effusions, septations and safely conduct invasive procedures. Recently sonographic septations are reported as significant predictor of tuberculosis. By combining these two entities, diagnostic yield can be increased tremendously for tuberculosis. Objectives: To evaluate the combined effect of sonographic findings of septations and pleural fluid ADA levels on the diagnostic yield for tuberculous pleural effusions. Patients and methods: This prospective study was conducted at the Pulmonology Outpatients Department of Gulab Devi Chest Hospital, Lahore from January 2016 till June 2018. Total 415 cases with age 14 years and above, having radiological evidence of pleural effusion and willing for ADA level estimation were included in the study. Detailed history, physical examination, X-ray chest, transthoracic ultrasound (TUS), haematological and biochemical reports were evaluated. Pleural fluid (PF) cytology, microbiology and biochemical analysis including pleural fluid ADA estimation was done. Data entered and analyzed in SPSS version 21. Results: Out of 415 cases, 380 (91.56%) were exudates. Statistical analysis of results after combining sonographic septations and PF ADA levels results showed sensitivity of 97.21%, specificity 91.22%, positive prediction 98.43%, and negative prediction of 85.24% for diagnosis of tuberculous effusion. Conclusion: Combining sonographic septations with PF ADA levels has high diagnostic yield and is recommended as effective tool for initial diagnosis of tuberculous pleural effusions
Keywords: Pleural Fluid; ADA levels; Sonographic Septations; Diagnosis; Tuberculous effusion